Critical Role of Platelet Glycoprotein Ibα in Arterial Remodeling. Issue 3 (March 2015) - Chandraratne, Sue; von Bruehl, Marie-Luise; Pagel, Judith-Irina; Stark, Konstantin; Kleinert, Eike; Konrad, Ildiko; Farschtschi, Said; Coletti, Raffaele; Gärtner, Florian; Chillo, Omari; Legate, Kyle R.; Lorenz, Michael; et al.
Abstract : Objective—: Arteriogenesis is strongly dependent on the recruitment of leukocytes, especially monocytes, into the perivascular space of growing collateral vessels. On the basis of previous findings that platelets are central players in inflammatory processes and mediate the recruitment of leukocytes, the aim of this study was to assess the role of platelets in a model of arterial remodeling. Approach and Results—: C57Bl6 wild-type mice, IL4-R/Iba mice lacking the extracellular domain of the glycoprotein Ibα (GPIbα) receptor, and mice treated with antibodies to block GPIbα or deplete circulating platelets were studied in peripheral arteriogenesis. Using a novel model of intravital 2-photon and epifluorescence imaging, we visualized and quantified the interaction of platelets with leukocytes and the vascular endothelium in vivo. We found that transient platelet adhesion to the endothelium of collateral vessels was a major event during arteriogenesis and depended on GPIbα. Furthermore, leukocyte recruitment was obviously affected in animals with defective platelet GPIbα function. In IL4-R/Iba mice, transient and firm leukocyte adhesion to the endothelium of collateral vessels, as well as leukocyte accumulation in the perivascular space, were significantly reduced. Furthermore, we detected platelet–leukocyte aggregates within the circulation, which were significantly reduced in IL4-R/Iba animals. Finally, platelet depletion and loss of GPIbα function resulted in poor reperfusion recovery as determined by laser Doppler imaging. Conclusions—: Thus, GPIbα-mediated interactions between platelets and endothelial cells, as well as leukocytes, support innate immune cell recruitment and promote arteriogenesis-establishing platelets as critical players in this process. Abstract : Supplemental Digital Content is available in the text.